Primary Urethral Carcinoma in a Bitch - Multimodal Treatment - Paiva, Felipe Noleto de [UNESP]; Ferrari, Bruno Santos; Silva, Michelle Lussac; Torquato, Lizandra de Fátima Brandão; Andrade, Max Ferreira de; Fernandes, Maria Eduarda dos Santos Lopes; Costa, Thiago Souza; Fernandes, Julio Israel (Universidade Federal do Rio Grande do Sul, 2022)
Background: Urethral tumors are uncommon in canines, represented predominantly by transitional cell carcinoma, marked by aggressive behavior associated with short life expectancy. Definitive diagnosis is achieved by histopathological analysis. Surgery associated with chemotherapy is the main therapeutic alternative. The aim of this paper is to report a case of primary transitional cell carcinoma of the urethra in a bitch, submitted to surgical treatment associated with conventional adjuvant chemotherapy and metronomic chemotherapy, achieving survival of 21 months, to date. Case: A 12-year-old bitch mixed breed was admitted at the Veterinary Hospital of Federal Rural University of Rio de Janeiro (UFRRJ), manifesting hematuria and urinary incontinence for one month. Physical examination indicated that vital parameters were within normal limits. Laboratory tests of blood count and serum biochemistry, urinalysis, culture, urinary antibiogram, and abdominal ultrasound were performed. The ultrasound image suggested a neoplastic urethral process. Because of the suspicion of neoplasm, a thoracic X-ray was performed, showing no evidence of metastasis. Computed tomography (CT) of the abdominal region was performed, revealing an expansive lesion in the urethra with loss of definition of the walls and urethral lumen extending to the level of the pelvic floor, measuring about 2.9 x 1.4 x 1.2 cm. After preanesthetic exams, the animal underwent resection and surgical anastomosis of the affected urethral region. The sectioned tissue was sent for histopathological analysis, with diagnosis of transitional cell carcinoma. Adjuvant chemotherapy was performed using carboplatin at a dose of 250 mg/m2 intravenously, every 21 days for 6 sessions. After completing the protocol, abdominal ultrasonography was performed again, which showed a cicatricial process in the urethral region of the surgical excision, with no sign of tumor recurrence. A metronomic chemotherapy protocol was then started with cyclophosphamide at a dose of 15 mg/m2 daily for 6 months, with periodic oncological follow-up. At the end of the period, the animal remained under periodic follow-up with ultrasound exams performed at 2-month intervals, and has been free from recurrence for 21 months until now. Discussion: Urethral neoplasms account for 0.5 - 2% of all canine tumors, and are represented mostly by transitional cell carcinomas. Clinical signs of urinary obstruction and hematuria are the most common, as reported in the patient in question. The definitive diagnosis is by histopathological examination. However, imaging tests such as computed tomography are important in the initial investigation and surgical planning. The indicated treatment is surgical resection of the mass with subsequent adjuvant chemotherapy or radiotherapy. The chemotherapy protocol associating cisplatin and piroxicam can achieve remission rates of 70%, but this association has a high nephrotoxic effect. In the present case, cisplatin was replaced by carboplatin in order to reduce the nephrotoxic effects of chemotherapy. The metronomic protocol using cyclophosphamide was used as maintenance therapy, at the end of the conventional chemotherapy protocol. Survival achieved was longer than that described in the literature in cases of transitional cell carcinomas in the urethral region. Therefore, multimodal therapy using surgery associated with conventional and metronomic chemotherapy, is an option in canines with urethral carcinoma.
Carcinoma uretral primário em uma cadela - tratamento multimodal
Keywords: canine; chemotherapy; surgery; urethral neoplasm